2016
DOI: 10.1007/s00296-016-3435-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in primary systemic vasculitis and potential drug therapies to reduce cardiovascular risk

Abstract: Cardiac involvement is common in primary systemic vasculitides and may be due to direct effect of the disease on the heart or due to therapy. We shall review involvement of the heart in the various forms of primary systemic vasculitis. Among anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV), eosinophilic granulomatosis with polyangiitis most commonly involves the heart. Involvement of the heart confers poorer prognosis in AAV, which is also complicated by increased risk of cardiovascular events.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 152 publications
1
35
0
3
Order By: Relevance
“…Nonspecific complaint in acute myocarditis such as dyspnea or chest pain is an underdiagnosed cause of acute heart failure 7 . Despite common presentation in admitted patients from this study, acute myocarditis has scarcely been reported in MPA 3 , raising the possibility of an overlooked diagnosis. The myocarditis-associated heart failure in MPA can have clinical symptoms and physical signs such as dyspnea and pedal edema mimicking the lung and renal involvement, respectively.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Nonspecific complaint in acute myocarditis such as dyspnea or chest pain is an underdiagnosed cause of acute heart failure 7 . Despite common presentation in admitted patients from this study, acute myocarditis has scarcely been reported in MPA 3 , raising the possibility of an overlooked diagnosis. The myocarditis-associated heart failure in MPA can have clinical symptoms and physical signs such as dyspnea and pedal edema mimicking the lung and renal involvement, respectively.…”
mentioning
confidence: 61%
“…The presence of cardiac insufficiency is recognized as a poor prognostic factor in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) 1 , and heart failure is an identified mortality risk factor for eosinophilic granulomatosis with polyangiitis (EGPA) 2 . Microscopic polyangiitis (MPA) has lower frequencies of myocardial involvement with rarely reported acute myocarditis presentation 3 . Rituximab (RTX) is a first-line induction therapy licensed for severe MPA with reduced ANCA titers and clinical remission 4 .…”
mentioning
confidence: 99%
“…Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare disease occurring exclusively in asthmatic patients [1], and classi ed as anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) [2]. Among 3 AAV-related disorders, cardiac involvement is most commonly observed in EGPA patients with a frequency ranging from 16 to 92% [3,4]. The therapy can be adapted for the presence of poor prognostic factors, i.e., ve-factor score (FFS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical endothelial injury as a result of chronic inflammation in BD has been associated with thrombosis and arterial stiffness, risk factors for ischemic heart disease (IHD) 1-4 . However, data regarding the association between BD and IHD and the impact of various risk factors on this association, is scarce [3][4][5] .…”
mentioning
confidence: 99%